2009
DOI: 10.1152/ajprenal.00268.2009
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose indomethacin after ischemic acute kidney injury prevents downregulation of Oat1/3 and improves renal outcome

Abstract: We have previously shown that expression of renal organic anion transporters Oat1 and Oat3 is diminished by prostaglandin E2 (PGE2) and that both transporters are downregulated after renal ischemia. Because PGE2 is increased after renal ischemia and is generated by cyclooxygenases (COX), we investigated the effect of the COX inhibitor indomethacin on expression of Oat1/3 after ischemic acute kidney injury (iAKI). iAKI was induced in rats by bilateral clamping of renal arteries for 45 min. Indomethacin (1 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 40 publications
17
40
0
1
Order By: Relevance
“…Inulin clearance was 0.58 Ϯ 0.077 ml/min (n ϭ 11) in untreated controls and 0.57 Ϯ 0.040 ml/min (n ϭ 9) in sham-operated animals, indicating that surgical intervention had no effect on glomerular filtration rate. These values agree well with previously published data (26), indicating that this model is reproducible and reliable. As expected, iAKI caused by I/R injury decreased inulin clearance to 0.19 Ϯ 0.023 ml/min (n ϭ 11).…”
Section: Effect Of N 6 -(1-iminoethyl)-l-lysine On No Levels and Renasupporting
confidence: 92%
See 2 more Smart Citations
“…Inulin clearance was 0.58 Ϯ 0.077 ml/min (n ϭ 11) in untreated controls and 0.57 Ϯ 0.040 ml/min (n ϭ 9) in sham-operated animals, indicating that surgical intervention had no effect on glomerular filtration rate. These values agree well with previously published data (26), indicating that this model is reproducible and reliable. As expected, iAKI caused by I/R injury decreased inulin clearance to 0.19 Ϯ 0.023 ml/min (n ϭ 11).…”
Section: Effect Of N 6 -(1-iminoethyl)-l-lysine On No Levels and Renasupporting
confidence: 92%
“…I/R injury was induced in rats by bilateral clamping of the renal arteries for 45 min followed by a reperfusion period of 24 h as described previously (26). Female Sprague-Dawley (SD) rats (200 -250 g body wt) were obtained from Charles River Wiga (Kissleg, Germany).…”
Section: In Vivo Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…(Feitoza et al, 2002;. The research on rats showed low-dose (1 mg/kg) IMT had a substantial protective effect on kidney function after AKI (Schneider et al, 2009). In recent studies, we set 1, 3, 5, and 7 mg/kg IMT treatment in the mice IRI model, and found that 5 mg/kg IMT was the proper dose in this study.…”
Section: Discussionmentioning
confidence: 79%
“…An increasing number of studies reported that pretreatment with IMT alone tended to reduce the renal damage after IRI (Schneider et al, 2009). Feitoza et al (2008 showed that pretreatment of mice with 5 mg/kg IMT could protect the renal function and reduce long-term renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%